2020
DOI: 10.1177/2058738420941762
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of resveratrol on estrogen deficiency-induced osteoporosis though attenuating NADPH oxidase 4/nuclear factor kappa B pathway by increasing miR-92b-3p expression

Abstract: Introduction: Resveratrol (RES) exhibits estrogen-like effects and has potential applications to treatment of osteoporosis caused by estrogen deficiency; however, the specific mechanism of action of RES remains unclear. Here, we examined the therapeutic effects of RES on ovariectomized (OVX) rats with osteoporosis and determined the underlying mechanism. Methods: We established an OVX rat model to study osteoporosis caused by estrogen deficiency. The treatment groups were given orally with RES (50, 100, and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…Recent studies have demonstrated that the expression levels of various miRNAs are significantly altered, which may be involved in the pathophysiological process of I/R injury, including miR-497, miR-1, and miR-181, which are related to neuroprotection [ 22 , 23 ]. Recently, a study has shown that miR-92b-3p, may be involved in the occurrence of oxidative stress injury during cerebral I/R induced by NOX4 overexpression, which eventually leads to the accumulation of oxygen free radicals and the death of neuronal cells from oxidative stress injury [ 24 ]. This study showed that miR-92b-3p was significantly decreased in a cerebral I/R injury rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the expression levels of various miRNAs are significantly altered, which may be involved in the pathophysiological process of I/R injury, including miR-497, miR-1, and miR-181, which are related to neuroprotection [ 22 , 23 ]. Recently, a study has shown that miR-92b-3p, may be involved in the occurrence of oxidative stress injury during cerebral I/R induced by NOX4 overexpression, which eventually leads to the accumulation of oxygen free radicals and the death of neuronal cells from oxidative stress injury [ 24 ]. This study showed that miR-92b-3p was significantly decreased in a cerebral I/R injury rat model.…”
Section: Introductionmentioning
confidence: 99%
“…The role of psychological stress and excessive cortisol secretion in oral disease such as OLP (Gaur et al, 2018) has been reported in several studies. Low levels of estrogen in post‐menopausal women lead to induction of the cellular immune system (Gameiro et al, 2010), increased activity of T‐Cytotoxic cells increases the production of inflammatory cytokines by activation of nuclear factor kappa B (NF‐κB) (Zhang et al, 2020), induce oxidative stress (Bourgonje et al, 2020), and decrease the production of anti‐inflammatory cytokines (Humberto et al, 2018; Upadhyay et al, 2010). The immunomodulatory, anti‐inflammatory, induction of cell proliferation, and cell protection effects of HSP70 have been reported in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…Penzkofer, D., et al proved the deletion of miR-92a will induce skeletal defects [22]. Increasing the expression level of miR-92b will suppress the Cathepsin K expression and Nox4/NF-κB signaling pathway, which can alleviate the progression of osteoporosis [23]. In the one hand the upregulated miR-92b accelerates osteogenesis of BMSCs.…”
Section: Discussionmentioning
confidence: 99%